E-Cigarettes and Cardiopulmonary Health. Issue 2 (8th February 2021) - Tarran, Robert; Barr, R Graham; Benowitz, Neal L; Bhatnagar, Aruni; Chu, Hong W; Dalton, Pamela; Doerschuk, Claire M; Drummond, M Bradley; Gold, Diane R; Goniewicz, Maciej L; Gross, Eric R; Hansel, Nadia N; et al.
Abstract: E-cigarettes have surged in popularity over the last few years, particularly among youth and young adults. These battery-powered devices aerosolize e-liquids, comprised of propylene glycol and vegetable glycerin, typically with nicotine, flavors, and stabilizers/humectants. Although the use of combustible cigarettes is associated with several adverse health effects including multiple pulmonary and cardiovascular diseases, the effects of e-cigarettes on both short- and long-term health have only begun to be investigated. Given the recent increase in the popularity of e-cigarettes, there is an urgent need for studies to address their potential adverse health effects, particularly as many researchers have suggested that e-cigarettes may pose less of a health risk than traditional combustible cigarettes and should be used as nicotine replacements. This report is prepared for clinicians, researchers, and other health care providers to provide the current state of knowledge on how e-cigarette use might affect cardiopulmonary health, along with research gaps to be addressed in future studies.